A survey of patient and medical professional perspectives on implementing osteoarthritis management programs for hip and knee osteoarthritis. (13th September 2022) - Wallis, Jason A.; Barton, Christian J.; Ackerman, Ilana N.; Sherwood, James; Kemp, Joanne L.; Young, Kirby; Jennings, Sophie; Trivett, Adrian; Brusco, Natasha K.
Abstract: Background: Strategies are needed to improve referral into, and uptake of, osteoarthritis (OA) management programs. This survey investigated and compared patients' and medical professionals' views around hip and knee OA management and factors impacting implementation of an osteoarthritis management program. Methods: As part of a mixed‐methods program of research, patients with hip or knee OA and medical professionals routinely involved in the management of OA, were invited to complete a comprehensive online survey. All data were analysed descriptively or using chi squared tests. Survey findings for factors perceived to impact implementation of an OA management programme were triangulated with previously reported qualitative data. Results: Fifty‐three patients (38 females, 15 males) and 32 medical professionals (orthopaedic surgeons, sports physicians, rehabilitation physicians, rheumatologists and general practitioners) completed the survey. Twenty‐eight patients (53%) had prior participation in the OA management programme (GLA:D ® ) and 19 medical professionals (59%) had previously referred patients to the programme. Of the participants with prior exposure, 21 patients (75%) and 15 medical professionals (79%) agreed the programme was beneficial. A higher proportion of medical professionals, compared to patients, believed weight loss (100% vs. 67%), injection therapy (50% vs. 21%), hip replacement (100% vs. 62%) and knee replacement (97% vs. 62%) were effective treatments, with no differences for all other treatments. The barriers and enablers identified for referral into, and participation in, an OA management programme mostly aligned to factors identified in previous related qualitative research. Divergent factors in the survey included patients concerns about doing exercise‐therapy with 81% (higher than expected) not reporting any concerns about exercising, and 19% (lower than expected) concerned about their OA joint, such as making their pain worse. Conclusions: This study has extended our understanding of barriers and enablers for referral into, and participation in, an OA management programme with a lower than expected number of patients being concerned about exercising due to their OA joint. Patients and medical professionals had positive views relating to the quality of the programme delivery, patient satisfaction and programme effectiveness. Medical professionals were more likely than patients to consider weight loss, injections and joint replacement as effective treatment options.